Composition and distribution of copepod populations in a tropical estuary - Mohd. Nor, Norhisyam (2013)
The purpose of this study was to analyze the copepod composition and distribution in a tropical estuary in Pendas river, Johor Malaysia. Samples were collected monthly for six month period at three stations in this study area located at an elevation of 5 m above sea level with coordinates 1°22'60" N and 103°37'59" E. Physico-chemical parameters in the study site such as salinity, dissolved oxygen (DO), pH, temperature, conductivity and total dissolved solid (TDS) were measured in situ using multiparameter water probe YSI professional model 556. Composite samples of chlorophyll a, and water samples for total nitrogen and total phosphorus analyses were collected by using Niskin water sampler. Copepod samples were collected using plankton net with 140 μm mesh towed horizontally at each station. A total of nine copepod genera from nine families were identified at the study site (river, estuary, strait). Copepod communities were dominated by adult copepod from the family Acartidae, Paracalanidae and Oithonidae in the study site. Copepod from genera Acartia sp were found alternately dominating copepod population at the river stations throughout the sixth month whereas in the estuary and strait stations, Paracalanus sp constantly dominated the total copepod populations. Species diversity index was highest (p < 0.05) in the strait compared to estuary and river sites.